Facile synthesis of multiple enzyme-containing metal–organic frameworks in a biomolecule-friendly environment1. Issue 69 (7th September 2015) - Wu, Xiaoling; Ge, Jun; Yang, Cheng; Hou, Miao; Liu, Zheng
<x xml:space="preserve">Abstract</x> A facile and simple method was proposed for the synthesis of multi-enzyme-containing metal–organic frameworks.